Less-Restrictive Food Intake During Labor in Low-Risk Singleton Pregnancies: A Systematic Review and Meta-analysis. Issue 3 (March 2017) - Ciardulli, Andrea; Saccone, Gabriele; Anastasio, Hannah; Berghella, Vincenzo
Abstract : OBJECTIVE: To evaluate benefits and harms of food intake during labor. DATA SOURCES: Electronic databases such as MEDLINE andClinicalTrials.gov were searched from their inception until October 2016. METHODS OF STUDY SELECTION: We included randomized trials comparing a policy of less-restrictive food intake with a policy of more restrictive food intake during labor. The primary outcome was the mean duration of labor. Meta-analysis was performed using the random-effects model of DerSimonian and Laird to produce summary treatment effects in terms of either a relative risk or a mean difference with 95% confidence interval (CI). TABULATION, INTEGRATION, AND RESULTS: Ten trials, including 3, 982 laboring women, were included. All the studies involved laboring singletons considered at low risk because they had no obstetric or medical complications that would increase the likelihood of cesarean delivery. In three studies, women were allowed to select from a low-residue diet throughout the course of labor. One study had honey date syrup as the allowed food intake. Five studies had carbohydrate drinks as food intake in labor. The last one was the only trial that allowed unrestrictive food intake. In the included studies, all women in the intervention group were allowed the assigned food intake until delivery, whereas women in a control group were allowed only ice chips, water, or sips of water until delivery. A policy of less-restrictive food intake was associated with a significantly shorter duration of labor (mean difference –16 minutes, 95% CI −25 to −7). No other benefits or harms in obstetric or neonatal outcome were noticed. Regurgitation during general anesthesia and Mendelson syndrome did not occur in either group. CONCLUSION: Women with low-risk singleton pregnancies who were allowed to eat more freely during labor had a shorter duration of labor. A policy of less-restrictive food intake during labor did not influence other obstetric or neonatal outcomes nor did it increase the incidence of vomiting. Operative delivery rates were similar. Abstract : Supplemental Digital Content is Available in the Text.A policy of less-restrictive food intake during labor is associated with a shorter duration of labor and does not influence neonatal outcomes in low-risk singleton gestations.